Remote Vehicle Monitoring and Tracking System - Lahab, Rauf (Universiti Teknologi Petronas, 2006)
Remote vehicle tracking and monitoring System has become one of the great systems in today industry. Many companies and institute are doing their research to enhance this system to another new level. Chapter one in this report gives a brief idea about the background of the study on what andwhy this system is develop. Theproblem statement and the scope of study are clearly stated in this section to indicate the main area of the system. Chapter two is the literature review whichis a finding or study about the system that already develop by other developer. It consists of various area of system that has relation with the basic idea which is meant for tracking and monitoring purposes. Chapter three is the section where the methodology use in developing the system and how the project works for the system is presented. The methodology is a step-by-step guide to develop the system in an organize way. The project works show how the system works using the diagram and its basic framework. Theframework developed is base on research being done and the best framework that suitable with the system that being develop is chose. Chapter four shows the result and discussion about the system development. The result is show in an illustrated figure. The discussion will give the basic idea on what is needed to be done and what should be improving for the system. Chapter five is the last section where in give the conclusion of the system development. It also gives the recommendation for any future upgrade or development on what need to be stressed out to build a sound system. in